Perkawinan Beda Agama dalam Perspektif Kompilasi Hukum Islam - Nova Fitri Aulia; Nurul Kamilah; Mia Yulistia (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
. Interfaith marriage represents a complex issue that sparks controversy in Indonesia's pluralistic society, particularly from the perspective of the Compilation of Islamic Law (KHI), which governs marriage law for Muslims in religious courts; Article 40 of the KHI explicitly prohibits marriage between Muslim men and non-Muslim women (kafir), although it permits Muslim men to marry women from the People of the Book (Jews or Christians) under strict conditions, grounded in Quranic verses such as QS. Al-Baqarah: 221, which forbids marriage to polytheists until they believe, and QS. Al-Mumtahanah: 10, which restricts ties with non-Muslims, aiming to preserve the purity of Islamic faith, prevent household conflicts due to differing beliefs, and ensure children's religious education is based on Islam; this provision aligns with Law No. 1 of 1974 on Marriage, Article 2 paragraph (1), which requires marriages to follow each party's religion, rendering interfaith marriages invalid under state law and potentially triggering legal issues such as child status, inheritance, and maintenance, even as clandestine or overseas practices persist, challenging law enforcement amid human rights dynamics and religious pluralism.